«Corinto di Zeus»: lirica ed epos nella Nemea VII di Pindaro (Nem. VII 102-105) (ACME, 2021)
The final lines of Pindar’s Seventh Nemean (Nem. VII 102-5) have often been read as a textual allusion to the Sixth Paean, and therefore as a confirmation of the so called “apology theory”. However, they can be easily understood within the poetic discourse of the ode as a summary of Pindar’s polemic attitude towards the mythical and cultural tradition, here represented by Homer (20-30) and the Panhellenic “vulgate” on Neoptolemus’ alleged impiety and death (33-50): the poet claims not to have «outraged Neoptolemus with unchangeable words» (ἀτρόποισι Νεοπτόλεμον ἑλκύσαι ἔπεσι), in contrast to the well-established and mendacious tradition on the hero. In this perspective, I suggest a possibly original reading of the phrase μαψυλάκας Διὸς Κόρινθος («the one who barks the refrain “Corinth of Zeus”») not only as an example of monotonous repetitiveness, but also of a distortion of the truth: I argue that the image triggers an allusive reference to the authority of the epic poet Eumelus of Corinth.